Pengaruh Penggunaan Media Pop-Up Book Terhadap Peningkatan Minat Belajar Peserta Didik Kelas IV Sekolah Dasar - Hamidah, Allinda; Nisa’, Muthoharotun (IBTIDA’, 2022)
The purpose of this study was to determine the effect of the use of Pop-Up Book learning media on the learning interest of fourth-grade students at Primary School. This research method uses the Quantitative Pre-Experiment method with the One Group pretest and post-test design model. Which uses treatment and measurement of 1 class with a quantitative approach. The sample in this study was class IV which amounted to 19 students. The instrument in this study was observed to see student activities, questionnaires, and documentation. The analysis technique used is descriptive statistical analysis technique and inferential statistical analysis. Based on the results of the pretest and post-test data analysis, the results of the pretest calculation are included in the sufficient category with a value of 59% in the value range of 40% ≤ KP ≤ 60%. And for posttest calculations, the result of the calculation is at the value range of 80% ≤ KP ≤ 100% with an average value of 83% included in the very good category. Based on the results of observations obtained the overall percentage is 94% which is included in the very good category. In addition, this research is also proven by using the normality test with the help of SPSS, and the results of the significance value 0,200 > 0,05, it can be concluded that the residual value is normally distributed. The results of the hypothesis test using the paired sample T-test with the help of SPSS with the provisions of Sig < α is 0,000 < 0,05 and t_count > t-table is 11,649 > 2,101 showed that there was a significant average difference between the pretest and posttest learning outcomes. Thus it can be said that H1 was received and H0 rejected, with this there is an effect of using Pop-Up Book media on increasing student interest in learning.